Geometry and art. Playing with circles in Early Childhood Education (Edma 0-6: Educación Matemática en la Infancia, 2022)
This article explains a didactic experience carried out in early childhood education center with 18 girls and boys aged 2-3 years. This project was based on the manipulation of the geometric shape of the circle through play and art.The aim is to analyze aspects linked to the learning of geometry, the acquisition of spatial notions and the development of the aesthetic sensitivity that underlies geometric shapes. Through this case study and using narrative and graphic-documentary techniques, the activities carried out and what happened in them are presented. The analysis of the results shows the adequacy of playful and artistic actions for learning the notions of Euclidean, topological and total space.
Keywords: Early Childhood Education; geometry; circle; art; playful